A description of sodium valproate, lamotrigine and levetiracetam consumption in the Western Cape public sector - Nicole Keuler; Yasmina Johnson; Renier Coetzee (South African Family Practice)
Background: The rational use of medicine is fundamental to ensure effective and safe patient medicine treatment, and hence, should be monitored. Undisputable evidence exists for the teratogenic risk factors associated with sodium valproate. Consequently, the Western Cape Department of Health introduced a policy (2019) recommending alternatives for valproate in women of childbearing age, including lamotrigine or levetiracetam as alternatives for patients on antiretrovirals. This study aimed to describe the change in the consumption of valproate, lamotrigine and levetiracetam after a policy implementation in public sector health facilities of the Western Cape, South Africa.